2019
DOI: 10.1111/jog.14173
|View full text |Cite
|
Sign up to set email alerts
|

Pilot study establishing a nomogram of yolk sac growth during the first trimester of pregnancy

Abstract: Aim: The yolk sac (YS) has been reported as a reliable predictor of adverse pregnancy outcomes, however, it has always been evaluated cross-sectionally with a single ultrasound per patient. We sought to validate the use of YS dimensions in serial ultrasounds throughout the first 10 weeks of singleton and multiple gestations.Methods: This was a prospective cohort study where YS diameters were serially obtained with 2D ultrasound in singleton and multiple gestations from 5 to 11 weeks. Nonparametric test were us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 11 publications
(17 reference statements)
0
5
0
Order By: Relevance
“…This study analysed their gestational sac, yolk sac, and germ biomeasurements. In [ 18 ], the authors studied the relationship between yolk sac shape and pregnancy outcome in pregnant women and found that yolk sac shape was significantly different in pregnancy outcomes. In [ 11 ], the authors believed that yolk sac abnormality could lead to embryo death.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study analysed their gestational sac, yolk sac, and germ biomeasurements. In [ 18 ], the authors studied the relationship between yolk sac shape and pregnancy outcome in pregnant women and found that yolk sac shape was significantly different in pregnancy outcomes. In [ 11 ], the authors believed that yolk sac abnormality could lead to embryo death.…”
Section: Discussionmentioning
confidence: 99%
“…In [ 17 ], binary logistic regression was utilized for ascertaining whether serum AMH levels played any role in the occurrence of a miscarriage or other independent factors were also involved for miscarriage such as ovarian response, age, and other confounding factors. In [ 18 ], the YS has been testified as a responsible forecaster of adversative pregnancy outcomes. YS diameters were obtained with 2D ultrasound gestations from 5 to 11 weeks.…”
Section: Introductionmentioning
confidence: 99%
“…Increased XEN and decreased ESC growth are hallmarks of stress responses of cultured ESC. It is interesting that ultrasound studies or early post-implantation human embryos show that when yolk sac to embryo size ratios increase, reporting a similar lineage imbalance in vivo, this associates with miscarriage (Detti et al, 2020a;Detti et al, 2020b). These data suggest a similarity in lineage imbalance of in the embryo in vivo, and similar effects in cultured ESC may predict miscarriage.…”
Section: Discussionmentioning
confidence: 94%
“…Overall, in women with known last menstrual period in spontaneous pregnancies or known date of ovulation or embryo transfer in pregnancies resulting from ART, a smaller than expected GSD has been reported by all authors as predictive of subsequent miscarriage despite a normal fetal cardiac activity [21][22][23][24][25][26][27]. Smaller CRL [22,28] and lower fetal heart rate (24,28,29] for gestational age have also been reported in pregnancies that subsequently miscarried whereas in those cases the yolk sac size has been described as normal [24], decreased [29] or increased [25,30,31]. The gestational sac and yolk sac sizes starts deviating from normality as early as 6 weeks of gestation followed by changes in CRL and fetal heart rate at 7 and 8 weeks [26].…”
Section: Discussionmentioning
confidence: 99%